Reforming the Regulatory Treatment of Sovereign Exposures in Banking Regulation - André Sterzel (Credit and Capital Markets – Kredit und Kapital, 2020)
The European sovereign debt crisis has shown the tight linkage between sovereign and bank balance sheets. In the aftermath of the crisis, several reforms have been discussed in order to mitigate the sovereign-bank nexus. These reforms include the abolishment of preferential government bond treatment in banking regulation. This paper gives a detailed overview of literature and data which are closely related to the existing preferential sovereign bond treatment in bank regulation and highlights the need for reforms especially in the euro area. Against this background, the following three regulatory reforms are described and discussed: (i) positive risk weights for government bonds in bank capital regulation, (ii) sovereign exposure limits, and (iii) haircuts for government bonds in bank liquidity regulation. The discussion focusses on the effects of these reforms for bank behaviour and financial stability.
Keywords: G18; H63; H12; G11; 330; sovereign bonds; preferential treatment; bank regulation; sovereign risk; financial contagion; regulatory reforms